A Retrospective Review of the International Journal of Islamic Economics and Finance (IJIEF) - Ujang Syahrul Mubarrok; Zufia Rahmawati; Dzikrulloh Dzikrulloh (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2022)
This study analyzes the articles published by IJIEF using a bibliometric analysis of data from the 52 papers that were published between 2018 and 2019. The VOSviewer software was used to illustrate the research topic map. The result showed that IJIEF published 52 articles with an average of 24.81 pages per article. IJIEF articles related to fintech and Islamic banks had the most citations. Furthermore, most authors preferred to publish their results in a collaborative mode than the single authorship mode. Authors and institutions from Malaysia are the largest contributors to IJIEF articles. The topics widely discussed in articles include Islamic banks and Islamic finance, as well as the Granger causality. These findings are expected to be useful for the editorial board to improve the publication of their articles.